The Roles of Knowledge Management in Project Management towards Organizational Performance - Alghail, Adnan Ali; Liu, Yao; Cheng, Jack Kie (Global Journal For Research Analysis(GJRA), 2017)
This paper reveals the roles of Knowledge Management (KM) and its importance in Project Management (PM) for gaining and achieving a high organizational performance, thus, this paper aims to explain the theoretical concepts of KM and PM and the signicance of KM in PM practices in the organizations environment and to identify the roles of KM toward PM. The fullment and usage of KM is essential for modern organizations that are looking to serve their stakeholders, increase business performance, strengthen competitiveness, and achieve a high reputation in global competitions. Therefore, it is pivotal for such existing organizations to explore and identify their KM roles and establish a KM contribution closely with their PM practices for the sake to have a recognized business functionality and advanced degree of organizational performance. It argues that identifying KM roles in PM has the potential to enhance the organizational performance and achieve strategic goals in ongoing project activities.